دراسة نسيجية للقناة الهضمية للخفاش Pipistrellus kuhli - إبراهيم نهلة; شلفة مها (Latakia University Journal -Biological Sciences Series, 2019)
تظهر الدراسة التشريحية والنسيجية للقناة الهضمية عند حيوانات الخفاش Pipistrellus kuhli التي تم جمعها من المناطق الساحلية في الجمهورية العربية السورية تشابهاً عاماً في البنية التشريحية والنسيجية مع القناة الهضمية للثديات الأخرى، إنما هناك تمايز في بعض البنى المتخصصة والناتج عن تأثير البيئة ونمط التغذية، حيث يكون المريء طويلاً نسبياً، والقسم الصدري أطول من قسم العنق لقصر العنق، والغلالة تحت المخاطية نامية جداً غنية بالألياف الكولاجينية. تم تحديد البنية النسيجية التفصيلية للمعدة والأمعاء الدقيقة والغليظة وتحديد الغدد المعدية والمعوية معاً عند العينات المدروسة. The anatomical and histological study of the digestive canal of the Syrian pipistrellus kuhli shows general similarity to the anatomical and histological study of the digestive canal of other mammals, but there are some specialized structures which are the result of the effect of environment and feeding mood. The esophagus is relatively long, the thoracic part is longer than the cervical part because the neck is long. The submucous layer is well developed and rich in collagen fibers. The exact histological structures of the stomach, the small intestine and the large intestine were identified, and the gastrointestinal glands in the studied samples.